Online Single Submission (OSS) Sebagai Instrumen Reformasi Birokrasi : Analisis Atas Transparansi dan Akuntabilitas Pelayanan Perizinan di Era Digital: Penelitian - Mika Anwarita Pakpahan; Irmanjaya Thaher (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research aims to analyze the effectiveness of the Online Single Submission (OSS) system as an instrument of bureaucratic reform in realizing transparency and accountability of licensing services in the digital era. The scope of the study includes the normative provisions underlying OSS and its implementation in practice, focusing on the gap between regulatory design and bureaucratic reality. The research method uses a normative juridical approach, with an analysis of laws and regulations, academic literature, and relevant secondary data. The results of the study show that OSS is able to simplify licensing procedures and improve access to information, but still faces obstacles in the form of weak central-regional data integration, limited apparatus capacity, and lack of substantive transparency in decision-making. The conclusion of the study confirms that OSS has great potential as a legal instrument to support the principle of good governance, but its effectiveness is not optimal. It is necessary to strengthen derivative regulations, improve the competence of the apparatus, and have a more comprehensive supervision mechanism so that OSS can truly become a means of bureaucratic reform that ensures legal certainty, transparency, and accountability of public services.